Drinking Ethics According to Hadith and Its Review Based on Science: Etika Minum Menurut Hadis Serta Tinjauannya Berdasarkan Sains - Faticha Sadiyah (Jurnal Living Hadis, 2022)
There are many ethics governed by religion, both related to personal habits, other people and God. This paper aims to describe the ethics of drinking based on hadis and how the interpretation of the hadis relates to science. The method used in this paper is the thematic hadis; collecting hadis with the keyword 'syariba'. Once collected, these hadits are interpreted and relevant to scientific explanations. The writer finds four categories. First, the prohibition of drinking while standing. It’s can make the kidneys unable to filter properly, digestive dysfunction, unable to provide optimal freshness to the body, resulting in stomach ulcers. Second, the prohibition to breathe in the container. It’s can cause acidity in the blood to increase, causing decreased kidney performance, can be exposed to Helicobacter pylori bacteria, and cause ulcers. Third, encouragement to pray. Prayer is able to calm and reassure, has an effect on blood cells. Fourth, the prohibition of using gold vessels. Eating containers of gold can affect blood and urine and can lead to Alzheimer.